THE ROLE OF CULTURAL EQUIVALENCE IN TRANSLATING HUMOR FROM ENGLISH INTO UZBEK IN SITCOM SUBTITLES - Olimova Dilfuza Zokirovna (Bright Mind Publishing, 2025)
In today's globalized world, translating humor is one of the most challenging tasks, especially when subtitling sitcoms. Humor is deeply rooted in culture, and its transmission requires not only linguistic competence but also knowledge of the cultural context. This article examines the role of cultural equivalence in translating English humor into Uzbek when subtitling sitcoms. The analysis is based on a comparison of original lines and their translations, as well as identifying the strategies used to achieve adequacy and preserve the comic effect.
Keywords: Cultural equivalence, translating, humor, sitcom subtitles.